2021
DOI: 10.21037/atm-20-4411
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus delbrueckii alleviates depression-like behavior through inhibiting toll-like receptor 4 (TLR4) signaling in mice

Abstract: Background: The intestinal flora can influence behavior through the microbiota-gut-brain axis and is closely related to the occurrence and development of nervous system diseases such as depression. Probiotics like Lactobacillus may regulate the balance of the intestinal flora and play an active role in preventing and treating depression.Methods: Eight-week-old C57BL/6J mice (n=32) were randomly and equally divided into a normal control group, a control + Lac group, a model group, and a model + Lac group. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
0
19
0
13
Order By: Relevance
“…Multiple clinical studies have found that probiotics could improve depression symptoms. [25][26][27][28] In animal studies, for instance, probiotics have also been found to improve depression-like behavior in rats and mice, [29][30][31][32] whereas others have found no difference between probiotics and placebos in improving depression symptoms. 33 Currently, more studies have shown that probiotics have a positive effect on depression symptoms, but the amount, type, and duration of probiotics in each study is inconsistent, and more studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies have found that probiotics could improve depression symptoms. [25][26][27][28] In animal studies, for instance, probiotics have also been found to improve depression-like behavior in rats and mice, [29][30][31][32] whereas others have found no difference between probiotics and placebos in improving depression symptoms. 33 Currently, more studies have shown that probiotics have a positive effect on depression symptoms, but the amount, type, and duration of probiotics in each study is inconsistent, and more studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of Lactobacillus and Bifidobacterium has an antidepressive effect when administered to rodents ( Arseneault-Bréard et al, 2012 ). A more recent report suggested that Lactobacillus suppresses inflammation, with decreases in toll-like receptor, NOD-like receptor and interleukin-1β, and exerts an antidepressant-like effect ( Qiu et al, 2021 ). Cytokines changes are well known to be implicated in the pathology of depression ( Himmerich et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study has showed that major depressive disorder patients have less Bifidobacterium or Lactobacillus ( Aizawa et al, 2016 ). In an experimental mouse lipopolysaccharide-induced depressive model, treatment with Lactobacillus delbrueckii inhibited depression-like behavior ( Qiu et al, 2021 ). Previous studies revealed that Lactobacillus paragasseri OLL2809 (formerly classified as L. gasseri ) ( Tanizawa et al, 2018 ) can induce an immune reaction ( Sashihara et al, 2006 ), and modulate anxiety and stress in young athletes ( Sashihara et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of L. acidophilus and L. rhamnosus in the drinking water of the 5xFAD mice transiently increased Lactobacillaceae species without improving the nesting score but displayed reduced plaque load in the hippocampus [ 93 ]. In a similar mouse model, L. delbrueckii was described as able to improve depression-like behavior through inhibiting toll-like receptor 4 (TLR4) [ 94 ]…”
Section: The Pre and Clinical Neurological Effect Of Probioticsmentioning
confidence: 99%